Comprehensive Review of Carbon Capture Technologies for Climate Change Mitigation - Vita Meylani; Nundang Busaeri; Ocky Karna Radjasa; Nurul Hiron; Frista Mutiara (Purnomo Yusgiantoro Center, 2025)
The emissions of carbon dioxide (CO2) significantly contribute to the rise in global temperatures and the exacerbation of climate change. Various initiatives have been undertaken to reduce CO2 emissions, notably through the adoption of carbon capture technologies. These technologies include Carbon Capture and Utilization (CCU), Carbon Capture and Storage (CCS), and the integrated approach of Carbon Capture, Utilization, and Storage (CCUS). Our study aims to elucidate the operational principles of CCU, highlight the benefits of carbon capture, and provide recent updates on the application of CCU and CCS in daily contexts. Utilizing a qualitative descriptive methodology through a literature review, we examine the primary sources related to CCU and CCS from various databases such as Scopus, Springer, Taylor & Francis, and Google Scholar, covering the period from 2014 to 2024. As a novelty, our review covers physical techniques like absorption, gas or membrane separation, and pressure-temperature manipulation, alongside chemical methods such as the adsorption of amine compounds. Furthermore, biological techniques, including fixation, are also utilized. The operational framework of carbon capture technology is structured around three main processes: pre-combustion, post-combustion, and oxy-combustion. Notably, carbon capture technology incorporates the cultivation of microalgae as a fixation strategy, which promotes not only environmental sustainability but also shows significant promise for future applications. This method effectively sequesters large quantities of CO2 while requiring minimal nutritional resources. The advantages of utilizing microalgae include enhanced efficiency in CO2 fixation compared to terrestrial plants, reduced contamination, and a relatively simple operational structure. It is evident that the adoption of carbon capture technology is expected to increase in the coming years, particularly in light of the ongoing challenges posed by climate change. Prospective advancements in carbon capture technology are then discussed based on the review result. Thus, our literature review contributes to promoting the broader implementation of carbon capture technologies.